Untreated HSV Leading to Neonatal Death - Sawyer, Meghan; Thomas, Sharon (Translation: The University of Toledo Journal of Medical Sciences, 2025)
We discuss a case of a 10-day-old infant who presented in fulminant early-onset sepsis due to HSV (Herpes Simplex Virus), the patient ultimately succumbed to illness due to septic shock. The patient’s mother received a diagnosis of HSV in the days following delivery. However, without a system in place to connect a maternal diagnosis to the infant, the baby was not treated empirically. We discuss the early signs and symptoms of neonatal sepsis, including those that were present in this patient. Further emphasis is placed on the importance of early detection and prompt treatment of HSV sepsis due to the high mortality rate of the disease, including the potential need for a notification system to inform pediatricians and family practitioners about maternal post-partum diagnoses.